Development of battery monitoring system for power generators: insights and experience - Nandan Ganesh, Jeyabalan; Shahnurriman, Abdul Rahman; Mohamad Hilman, Nordin *; Norhidayu, Rameli; Muhammad Mokhzaini, Azizan; Nur Hazirah, Zaini; Izzuddin, Mat Lazim; Wong, Brandon Kai Yi (Semarak Ilmu Sdn Bhd, 2025)
The increasing dependence on battery monitoring systems (BMS) by power generators highlights the critical role of the former in ensuring continuous power operation and supply in commercial and residential facilities. This paper details the development of a BMS specifically tailored for monitoring Nickel-Cadmium (Ni-Cad) batteries at Jayalax Resources. The system provides near real-time data on essential metrics such as voltage, current, temperature, internal resistance, and state of charge (SOC) for each individual battery cell, all presented through an intuitive online dashboard. Additionally, the BMS features automated email notifications and alerts for critical conditions, including low voltage, high temperature, and significant SOC drops, ensuring timely intervention for remedial actions. The successful deployment of this system across various commercial and residential buildings in the Klang Valley has minimized the need for frequent manual inspections, reduced human error, and generated significant cost savings for Jayalax Resources. Insights gained from this project underscore the importance of robust monitoring solutions in optimizing battery performance and reliability in generator applications.